A Legal and Organizational Prospects for Improvement the Placement Process of the State Order for Specialists Training - Pyvovar, Yuriy; Pyvovar, Iryna; Iurynets, Julia (International Journal of Engineering and Technology, 2018)
Since 2013 with the gradual integration of Ukraine into the European and Global education space, there is a need to reduce the state’s financial expenses on specialists training and to change the principles of the formation, placement and performance (this triad represents the consecutive stages) of the mechanism of the governmental order in the field of education. Thereof it is suggested to determine the main objective, namely, prospects for improvement the mechanism of organization and legal groundwork for effectuation of placement of the governmental order for the specialists training for the state needs. The main results of the work became: firstly, the systematization of subjects involved in the process of placing the governmental order for specialists training. It was established that the main organizational guarantor in this process is the Cabinet of Ministers of Ukraine; the main coordinator is the Ministry of Economy and Development of Ukraine; the main performers of the order placement are governmental customers; placement targets are government performers. Secondly, two forms of administrative procedures for the performance of the governmental order placing are distinguished: 1) the public procedure of the competition for performers of the governmental order; 2) simplified (non-competitive) procedure for the appointment of performers of the governmental order. Within these procedures, organizational (institutional) and legal guarantees of their performance are described. The new achievements of the study became suggestions: firstly, introduction of a competitive procedure in the placement process of the governmental order for specialists training for the law enforcement agencies, as well as the implementation of a contractual procedure ofÂ signing state contracts for the performance of the governmental order between law enforcement agencies (governmental customers) and performers of the governmental order; secondly, to legalize in the law the procedure of conducting a competition among educational institutions of different departments with the purpose of choosing suitable ones for the governmental order performance; thirdly, to empower the Ministry of Economy and Development of Ukraine to agree the provisions of all governmental customers, the work of the Competition Committee on the selection of performers of the governmental order, as well as on the development of a typical procedure for the work of such Committees. Â Â